Spontaneous transformation of vestibular schwannoma into malignant peripheral nerve sheath tumor - Belyaev, Artem; Usachev, Dmitry; Shimansky, Vadim; Odamanov, Dzhemil; Shishkina, Lyudmila; Ryzhova, Marina; Golanov, Andrey (Asian Journal of Neurosurgery, 2018)
Although radiosurgery-induced transformation of vestibular schwannoma (VS) into malignant peripheral nerve sheath tumor (MPNST) is being widely discussed, little attention is paid to the spontaneous transition of these tumors. Although the pathogenesis of this phenomenon remains uncertain, growing number of reported cases might call to notice them. We present a case of a 29-year-old woman who suffered right-sided hearing loss which remained untreated for 4.5 years. Magnetic resonance imaging revealed a right cerebellopontine tumor and the patient underwent tumor removal through retrosigmoid approach. Pathologically, the tumor was benign acoustic schwannoma with increased Ki-67 8%–10%. The tumor relapsed only 6 months later and was removed again-this time it was malignant peripheral nerve sheath tumor MPNST. The patient was treated with stereotactic radiotherapy, but despite that tumor growth was observed again and she underwent the third operation. Later on, tumor progression was noted with multiple intraaxial metastases and patient died 17 months after the diagnosis of MPNST had been confirmed. This is a seventh documented case of spontaneous transformation of VS into MPNST, which is clinically important for recording.
Keywords: Malignant peripheral nerve sheath tumor; malignant transformation; vestibular schwannoma